GMP‐Compliant Process for the Manufacturing of an Extracellular Vesicles‐Enriched Secretome Product Derived From Cardiovascular Progenitor Cells Suitable for a Phase I Clinical Trial - Camille Humbert; Chloé Cordier; Iouri Drut; Michele Hamrick; Jacquelyn Wong; Valérie Bellamy; Justine Flaire; Kiranmayee Bakshy; Florent Dingli; Damarys Loew; Jérôme Larghero; Jean‐Roch Fabreguettes; et al. (Journal of Extracellular Vesicles)
ABSTRACT Extracellular vesicle (EV)‐enriched secretomes are emerging as a new and innovative therapeutic option in the field of regenerative medicine. The clinical use of EV‐enriched secretome‐based products requires manufacturing processes and quality control (QC) testing that comply with current good manufacturing practice (GMP). The goal of this work was to develop a robust and reproducible large‐scale GMP‐compliant process for the production of an EV‐enriched secretome derived from cardiovascular progenitor cells (CPC), including the vesiculation of CPC, purification and concentration of the product; and sterilising filtration. QC strategies for in‐process and release testing of an investigational medicinal product (IMP) were developed to guarantee quantity, safety, purity and identity. The IMP showed biological activity and was non‐immunogenic in vitro, and showed no signs of toxicity or tumour development in vivo. The IMP was approved for use in a single‐centre Phase I clinical trial by the French National Agency for Medicines and Health (ANSM) for the treatment of heart failure. The IMP is stored between –65°C and –85°C and can be easily diluted by the hospital pharmacy for infusion to the patient. This work represents a major advance for the use of CPC derived EV‐enriched secretomes as a biological drug for cardiac clinical applications. Trial Registration: ClinicalTrials.gov identifier: NCT05774509